Eksplorasi Cendawan Dark Septate Endophyte Asal Pertanaman Karet (Hevea brasiliensis) Wilayah Sumatra Utara - Andriyanto, Mochlisin; Triyoyani, Agustina; Sri Sulastri, Yustina; Dalimunthe, Cici Indriani (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2024)
Andriyanto, M., Triyoyani, A., Sulastri, Y. S., Dalimunthe, C. I. (2024). Exploration of dark septate endophyte fungi in north sumatra rubber plantations. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-12 Tahun 2024, Palembang 21 Oktober 2024. (pp. 313–322). Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Dark Septate Endophytes (DSE) are non-pathogenic microorganisms that ubiquitous root-colonizing fungi with a wide range of host plants. DSE biodiversity in the rubber plantations of North Sumatra has not been investigated. The research objective was to collect indigenous DSE isolates from rubber plantations. The research was conducted at the Plant Protection Laboratory, Sungei Putih Research Unit, Rubber Research Center in Deli Serdang. This research consisted of several stages, namely DSE investigated 14 soil samples taken from rhizosphere of healthy rubber plant in the area of Serdang Berdagai, Tebing Tinggi, Labuhan Batu Utara, Rantauprapat, Asahan, and Tapanuli Selatan. The exploration is followed by selecting DSE (dark septate endophytes) through indirect soil baiting techniques and pathogenicity test of DSE isolates. The research was conducted at the Plant Protection Laboratory, Sungei Putih Research Unit, Rubber Research Center in Deli Serdang. The results showed that height of chinese cabbage ranged 3,69- 5,17 cm, and number of leaves ranged 4,80-6,16 over the course of one month. The average DSE isolation rate was found to be 12,87%. The colony growth of isolates measured between 15,31 and 50,72 cm² in eight days after incubation, and the pathogenicity test had ability to promote chinese cabbage seed germination by 65,50- 70,60%. The present study showed that five DSE isolates from rubber plantation can be used as indigenous DSE and identified as having potential for development.